Disordered migration processes and global health - Jane Francinete Dantas; Rosângela Maria Morais da Costa; Aliete Cunha Oliveira; Joaquim Luís Medeiros Alcoforado (DST, 2021)
Introduction: Various territorial crises have marked humanity, causing precarious and irregular population displacements with an impact on the health of the population assigned to the waiting territories. Objective: This study sought to assess the impacts of the recent displacement of Venezuelans, amid the syphilis epidemic in Brazil, in the period from 2016 to 2019. Methods: This was a qualitative study with bibliographic design, in which searches were carried out in the Notifiable Disease Information System (SINAN), in the Virtual Health Library (VHL), in Google Scholar, also going through databases referenced in the health area, such as Latin American Literature in Health Sciences (LILACS), Medical Literature Analysis and Retrieval System Online (MEDLINE) and Nursing Database (BDENF). Results: The study showed that the disorderly displacement of Venezuelans had an international and local impact, culminating in the precariousness and overload of essential health services, shortage of medicines and supplies, an increase in the number of patients, resurgence of the measles outbreak in Brazil and an increase in the incidence of sexually transmitted infections such as syphilis. It was found that in the SINAN compulsory notification forms, there is no specific field for nationality, which makes it difficult to identify foreigners with syphilis, as well as the planning and monitoring of coping measures. Conclusion: As this is a challenging, conflicting theme, perceived as transversal, with micro-territorial, macro-regional, national and international implications, there is a need for more studies from a transdisciplinary approach to understand, analyze, prospect and provide a structured proposal for confronting the problematic evidenced in this work.